Análise do impacto do estilo de liderança do presidente Donald Trump na política externa de Washington para Pyongyang - Pontes, Lucas Leite Rangel de (2021)
Is it possible to extract personal characteristics of President Donald Trump by analyzing the content of his interviews? From these personal characteristics can sketch a leadership style and know his influence in the decision-making process? Objectives: This research examines the personal characteristics and influence of Donald Trump's leadership style in the decision-making process in the foreign policy of the United States of America. Method: The president's personal characteristics and leadership style will be studied from the perspective of the leadership traits analysis model suggested by Hermann (2005a; 2005b; 2005c). 155 spontaneous responses to interviews distributed in four years of the presidential term were encrypted and checked using the ProfilesPlus - LTA Classic software, extracting the leader scores in seven traits (belief in ability to control events, need for power, distrust, self-confidence, conceptual complexity, in group bias and task orientation) that, systematized according to the leadership traits analysis model, answer three central questions of the leadership style: does the leader respect or challenge restrictions?; is the leader open or closed to contextual information?; what are the motivations of the leader? Results: Based on the framework about the leadership style, the research follows in assessing the impact of this style and its characteristics in the decision-making process within a case study of Washington's foreign policy towards Pyongyang. Donald Trump had distinctive traits in “need for power and in group bias”, and an opportunistic leadership style.